Leading Indicators of Business Cycles in Malaysia and the Philippines - Wenda Zhang; Juzhong Zhuang (Asian Development Bank (ADB), 2002)
This paper attempts to construct leading indicator systems for the Malaysian and Philippine economies using publicly available economic and financial data, with a view to predicting turning points of growth cycles in the two countries. The results show that during the sample period of January 1981-March 2002, the composite leading index constructed from six individual leading indicators is able to predict all the nine turning points in industrial production in Malaysia, with an average signal leading time of 1.5 months for peaks and 3.4 months for troughs; and seven out of the eight turning points in manufacturing production in the Philippines, with an average signal lead time of 5.8 months for peaks and 6 months for troughs. This prediction performance is comparable to that of leading indicator systems of the G-7 economies maintained by the Organisation for Economic Co-operation and Development.
hdl:11540/2078
Keywords: 330; Wirtschaftsindikator; Konjunktur; Malaysia; Philippinen; Konjunktureller Wendepunkt